Rumusan Strategi Pengembangan Ekspor UKM Sepatu di Surabaya dengan Menggunakan Pendekatan ANP - Muhammad Jaharnsyah; Trisita Novianti; Ernaning W. (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
Surabaya has been developing a small and medium enterprises which one of them is village shoe. Small andmediums enterprises shoe has 140 units. However conditions of small and medium enterprises are nothingexport yet. This study wanted SMEs can be export product. This research use a method Delphi for choose acriterion what affects the development of export SMEs and then continued with modeling of using the methodANP and finally get the ranking of highest weight is linkage the material. Strategy that use is mappingsupplier what could give credit material. Strategic used is (1 ) give facility and increase quality SDM andthen taken worker by government and UKM, (2) mapping supplier who can giving credit material, (3) followinternational event or national event and add referensi shoe model with folowing trend.